2013
DOI: 10.1016/j.aap.2013.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Can we improve clinical prediction of at-risk older drivers?

Abstract: Objectives To conduct a pilot study to evaluate the predictive value of the Montreal Cognitive Assessment test (MoCA) and a brief test of multiple object tracking (MOT) relative to other tests of cognition and attention in identifying at-risk older drivers, and to determine which combination of tests provided the best overall prediction. Methods Forty-seven currently-licensed drivers (58 to 95 years), primarily from a clinical driving evaluation program, participated. Their performance was measured on: (1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 52 publications
5
64
0
Order By: Relevance
“…We focused on studies that primarily included drivers with suspected or confirmed cognitive impairment, including dementia. Eight studies, including three from the current authors, were found (Bowers et al, 2013;Carr et al, 2011;Hoggarth et al, 2013;Innes et al, 2007Innes et al, , 2011Lincoln et al, 2006;Ott et al, 2013;Snellgrove, 2000). These studies are summarized in Table 1.…”
Section: Literature Reviewmentioning
confidence: 92%
See 3 more Smart Citations
“…We focused on studies that primarily included drivers with suspected or confirmed cognitive impairment, including dementia. Eight studies, including three from the current authors, were found (Bowers et al, 2013;Carr et al, 2011;Hoggarth et al, 2013;Innes et al, 2007Innes et al, , 2011Lincoln et al, 2006;Ott et al, 2013;Snellgrove, 2000). These studies are summarized in Table 1.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Two of the eight studies (Bowers et al, 2013;Lincoln et al, 2006) did not report the selection process of the variables used during model construction. One study (Snellgrove, 2000) used an enter approach while the remainder used some type of stepwise procedure (forward or backward).…”
Section: Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…These declines may be a factor in intersection collisions, and although a variety of measures have been used to predict performance in older drivers, a recent study included multiple-object tracking as one (e.g. Bowers et al 2013). However, the problem with correlational evidence of this type is that if a relationship between tracking and driving performance exists, it is unclear whether it is because multiple-object tracking is actually used in driving or whether it just correlates with other abilities that are used in driving.…”
Section: Objectivesmentioning
confidence: 99%